Legal Protection for Victims of Domestic Violence in Indonesia - Andi Putri Amelia Ibbar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study investigates the legal protections available for victims of domestic violence in Indonesia. It comprehensively analyses existing laws, policies, and support systems designed to safeguard victims and hold perpetrators accountable. The research highlights significant gaps in legal protections, including the inadequacy of current legislation, enforcement challenges faced by law enforcement agencies, and the societal stigma that victims often encounter. Through qualitative methods, including interviews with legal experts, social workers, and victims and a thorough review of relevant case law, the study aims to identify the barriers that prevent victims from accessing justice. Key findings reveal that while some legal frameworks are in place, they often lack effective implementation, leaving many victims vulnerable. Additionally, the research emphasizes the need for a more coordinated response among various stakeholders, including government agencies, NGOs, and community organizations, to create a supportive environment for victims. Recommendations for improving legal frameworks and support services are presented, aiming to ensure that victims receive adequate protection and have meaningful access to justice. By addressing these issues, this study contributes to the ongoing discourse on enhancing legal protections for domestic violence victims in Indonesia.